Chemical Properties of Natural Fiber Composites and Mechanisms of Chemical Modifications - Gupta, Anu; Kumar, Ajit (Asian Journal of Chemistry, 2011)
In recent years, natural fibers reinforced composites have received a strong attention because of their light weight, nonabrasive, combustible, nontoxic, low cost and biodegradable properties. However, the lack of good interfacial adhesion, low melting point and poor resistance towards moisture make the use of natural fiber reinforced composites less attractive in a number of applications. Chemical treatment of the natural fibers can clean the fiber surface, chemically modify the surface, stop the moisture absorption process and increase the surface roughness. A number of specific chemicals are used for chemical modifications of these composites. Such chemically modified are being used increasingly for engineering applications (particularly under hard working conditions). Over the life-span of the composites, the environmental conditions also affect the behaviour of composite to a large extent. Thus, it becomes necessary to take care of the chemical properties of composites to ensure their long term stable behaviour in the practical applications. This paper outlines the chemical properties of natural fibers composites and discusses the latest trends in chemical modification mechanisms. A number of commonly used natural composites have been cited as examples in different mechanisms.